PENGEMBANGAN SENAM SUPER KIDS CERIA PADA PEMBELAJARAN PJOK AKTIVITAS RITMIK SISWA KELAS V SD NEGERI 1 NGAWENSARI - Tarisa Alienda; Donny Anhar; Titis Nurina (Journal of Physical Activity and Sports (JPAS), 2026)
This study was conducted to design and develop the Super Kids Ceria Gymnastics model as an innovative approach to rhythmic activity learning for elementary school students. The research applied a Research and Development (R&D) design based on the Borg and Gall development framework. The study took place at SD N 1 Ngawensari, involving 20 fifth-grade students in the small-scale trial and 115 students from grades I to VI in the large-scale implementation. Data were gathered using expert validation instruments, student response questionnaires, observation sheets, and pretest–posttest pulse rate measurements. The findings indicated that expert validation achieved an average score of 77.00%, categorized as Good. The small-scale trial resulted in a score of 80.69% (Good category), while the large-scale trial demonstrated an improved result of 84.90%, classified as Very Good. Furthermore, the paired sample t-test produced a significance value of 0.000 (<0.05), confirming a statistically significant increase in students’ pulse rates after participating in the gymnastics activity. Therefore, the Super Kids Ceria Gymnastics model can be considered both appropriate and effective as a rhythmic learning strategy in elementary school physical education.